1960
DOI: 10.1111/j.1365-2672.1960.tb00184.x
|View full text |Cite
|
Sign up to set email alerts
|

Tellurite‐egg Agar, a Selective and Differential Medium for the Isolation of Coagulase Positive Staphylococci

Abstract: SUMMARY: The preparation and use of tellurite‐egg agar (TEA), a medium for the isolation of coagulase positive staphylococci, are described. The medium, based on that of Ludlam (1949), was non‐inhibitory to coagulase positive staphylococci and colonies on it of these organisms could easily be distinguished from contaminating types. Comparisons were made between the medium and three other media in common use for the isolation of coagulase positive staphylococci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1962
1962
1975
1975

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…Tests on the tellurite, glycine medium of Zebovitz et al (1955) confirmed previous observations by Hoeprich, Croft & West (1960), Sevel & Plommet (1960 and Innes (1960) that it is inhibitory to many strains of Staph. aureus on primary isolation.…”
Section: Preliminary Experimentssupporting
confidence: 77%
See 3 more Smart Citations
“…Tests on the tellurite, glycine medium of Zebovitz et al (1955) confirmed previous observations by Hoeprich, Croft & West (1960), Sevel & Plommet (1960 and Innes (1960) that it is inhibitory to many strains of Staph. aureus on primary isolation.…”
Section: Preliminary Experimentssupporting
confidence: 77%
“…Phage typing is a valuable means of identifying enterotoxic strains of staphylococci (Allison, 19491, but only when the phage type has been isolated from a food incriminated in a food poisoning outbreak (Elek, 1959). The in vitro enterotoxin test of Levi, Matheson & Thatcher (1956) awaits confirmation, as does the suggested correlation between ability to cause opacity in egg yolk broth and enterotoxin production (Innes, 1960). If the latter relationship is confirmed it could be said that enterotoxic types are mainly of human origin, as most strains of Staph.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To facilitate the examination of large numbers of strains, a solid egg yolk medium was developed by one of the authors (B. J. C.); similar media have been described by Colbeck (1956), Carter (1960), Innes (1960 and Baird-Parker (1962). The formula which was found to give optimal results in tests which will be described separately (Collins, to be published) was yeastrel agar containing 5 % egg yolk and 5 % horse serum.…”
Section: Methodsmentioning
confidence: 99%